Connecting the poor: the internet, mobile phones and financial inclusion in Africa. Issue 6 (10th September 2018) - Evans, Olaniyi
Abstract : Purpose: The increased adoption of internet-enabled phones in Africa has caused much speculation and optimism concerning its effects on financial inclusion. Policymakers, the media and various studies have all flaunted the potentials of internet and mobile phones for financial inclusion. An important question therefore is "Can the internet and mobile phones spur the inclusion of the financially excluded poor? This study therefore aims to examine the relationship and causality between internet, mobile phones and financial inclusion in Africa for the 2000-2016 period. Design/methodology/approach: The empirical analysis followed these three steps: examination of the stationarity of the variables; testing for the cointegration; and evaluation of the effects of the internet and mobile phones on financial inclusion in Africa for the 2000-2016 period using three outcomes of panel FMOLS approach and Granger causality tests. Findings: The empirical evidence shows that internet and mobile phones have significant positive relationship with financial inclusion, meaning that rising levels of internet and mobile phones are associated with increased financial inclusion. There is also uni-directional causality from internet and mobile phones to financial inclusion, implying that internet and mobile phones cause financial inclusion. The study also shows that macroeconomic factors such as capital formation, primary enrollment, bank credit, broad money, population growth, remittances, agriculture and interest rate, as well as institutional factors such as regulatory quality are important underlying factors for financial inclusion in Africa. Originality/value: In the literature, there is a dearth of research on the internet, mobile phones and financial inclusion, especially in Africa. Most of the related studies are conceptual and micro-based, with little empirical attention to the relationship and causality between internet, mobile phones and financial inclusion. In fact, this dearth of rigorous empirical studies has been attributed as the main cause of inadequate policy guidance in enhancing information communication technologies (Roycroft and Anantho, 2003 ), despite saturation levels in developed economies. This study fills the gap by evaluating the effects of the Internet and mobile phones on financial inclusion for 44 African countries for the 2000-2016 period.